The Influence of System Quality, Information Quality, and Service Quality on Student Satisfaction in Using E-Learning at Universities in Jambi - Viola, Mayshel Adinda; Yamkee, Abduhakim Kajee; Vilanti, Friska Aqilah; Swastini, Swastini (Educational Leadership and Management Journal, 2024)
This research aims to analyze the influence of system quality, information quality and service quality on student satisfaction in using e-learning in universities throughout Jambi Province. The research method used is a quantitative approach with a survey design and Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to analyze the relationship between variables and the suitability of the research model. The research sample was determined using the Convenience Sampling technique with a total of 207 respondents taken from a population of 114,134 students at 7 universities in Jambi City. The research results show that system quality, information quality, and service quality have a significant influence on student satisfaction in using e-learning. This study emphasizes the importance of good system quality, accurate and complete information, and responsive services to increase user satisfaction in the context of e-learning. It is hoped that these findings can become a reference for educational institutions in improving the implementation of e-learning to make it more effective and satisfying for users.